Optimizing Happiness at Work in Female Correctional Officer - Anggun Resdasari Prasetyo (Journal of Educational, Health and Community Psychology, 2019)
Happiness at work is a central issue that needs to be investigated within the scope of work psychology, especially as a means for building positive characteristics of female correctional officers both individually, family and institutions. the subjects involved were 170 female correctional officers in Cipinang Class I, Narcotics Prison, Pondok Bambu Class IIA, and Salemba Class IIA. The main method to be used in this study was to use a quantitative approach. In this study the researchers conducted several objectives, including: 1.) Testing psychometric properties of work happiness measurement tools on the Oxford Happiness Questionnaire and Work Happiness Scale, 2.) Identifying factors that predict Work Happiness in Women's Correctional Officers, and 3.) Test the differences in work happiness in terms of work units. The results of the multiple linear regression analysis using the stepwise model show that the psychosocial climate safety and work engagement variables contribute 33.7% to work happiness, with a value of R = 0.581, F = 40,445, p